The impact of a continuing education programme on the adoption of nickel–titanium rotary instrumentation and root‐filling quality amongst a group of Swedish general dental practitioners. (20th March 2014) - Dahlström, L.; Molander, A.; Reit, C.
Abstract Introduction The aim of the study was to test the hypothesis that a further education programme relating to nickel–titanium rotary instrumentation (NTRI), with the concurrent activation of social/professional networks amongst all general dental practitioners (GDPs) in a public dental service in Sweden, would increase the adoption rate and improve root‐filling quality. Material and method To activate the networks, the GDPs at the 25 clinics elected training coaches from amongst themselves. The coaches were educated by a specialist and were then free to organise and conduct the training of the local GDPs. However, collective hands‐on training and discussions were mandatory. Lectures were held by an endodontist. The rate of adoption and root‐filling quality was evaluated just before and 6 months after the education. Statistical tests were performed with chi‐square using a 95% confidence interval. Results Nickel–titanium rotary instrumentation was adopted by 88%. Excellent root fillings (score 1) increased from 45% to 59% (P = 0.003). The rate of poor‐quality root fillings (score 4 and score 5) was not affected. The quality ratio (score 1/score 5) increased from 5.36 (118/22) to 9.5 (133/14). Eleven dentists (17%) at nine different clinics produced 49% of the poor‐quality root fillings (score 4 and score 5). Seventy‐three per cent of these dentists stated that they had adopted NTRI. Conclusions The introduction of NTRI will increase the adoption rate and the frequency of good‐quality root fillings. However, it will not overcome the problems associated with dentists producing a low‐quality level, even if a local professional network is activated.